Prototype Smart Traffic Light Otomatis Berbasis Atmega-328 dengan Sensor Jarak - Nahdia Rupawanti BR (Universitas Islam Lamongan, 2019)
Research design of automatic traffic light control based on ATMega328 microcontroller with proximity sensor aims to get a control system that can be used to reduce congestion at intersections that have a traffic light system.The method of in this study are qualitative and experimental methods. The trial of process done by testing the infrared sensor. The infrared sensor test results obtained an average value of 16 seconds and the average value of the light dependert resistor sensor 66 seconds. Result of this study are that the design design model is useful in the use of infrared waiting time stability 16 seconds - 20 seconds while the light dependert resistor is 66 seconds 70 seconds in the traffic light system.